RESTAURANT BUSINESS: INNOVATIVE CHANGES IN THE CONVERSION OF COVID VIRUS 19 - PRYLEPA, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the innovative changes in the restaurant business in the context of the spread of the COVID 19 virus in Ukraine and abroad. It was the restaurant establishments in the conditions of COVID 19 that were forced to react quickly to the new conditions and needs of the quarantine services market. The advantages of applying innovative changes in the restaurant business are indicated. It is determined that the culture of food delivery and online ordering began to develop at an incredibly fast pace in Ukraine and abroad. Applications such as Delivery.com, Raketa, Glovo are becoming one of the most popular food delivery applications. We analyzed a convenient service for ordering - telegram bots, the essence of which is that a person can not only electronically view the proposals of the institution, but also track all stages of preparation of the ordered dish, from receipt of the order to ready to receive. This characteristic of the latest technology - restaurants without ticket offices and sellers. It has been noted that self-service, whether through drive windows, the Internet or digital platforms, is fast reaching the restaurant business, and the potential of this market is huge. It is determined that mobile applications in virtual objects have led to the emergence of creative directions for the development of restaurant businesses and their approach to consumers. Today, the consumer can order culinary meals without leaving home, work or in other various situations that limit the appropriate time to visit the restaurant business. RFID technologies have also become widely used. The essence of the technology is in placing RFID-tags near restaurants, which can be read by special portable devices via Wi-Fi, Bluetooth or mobile communication. It was concluded that the strategy of adaptation of each of the restaurant businesses to quarantine conditions was unique, but they all used similar methods to reorganize their activities.